Conflicting Reports? Augustus’ Relationship with the Senate and Established Order During His Road to Power in Res Gestae, Velleius Paterculus, Suetonius, and Tacitus - Poulsen, Aske Damtoft (Histos, 2023)
This paper explores four accounts of Augustus’ relationship with the senate and established order during his early career, with particular focus on his involvement in the civil wars: his own Res Gestae, Velleius Paterculus’ Roman History 2.59–89, Suetonius’ Life of Augustus, and Tacitus’ Annals 1.1–10. Through comparison of these—at times wildly conflicting—accounts, it demonstrates that relations with the senate play a significant role in verdicts on the first emperor’s rise to power. In Res Gestae Augustus executes the will of the senate from start to finish, in Velleius Paterculus he is temporarily forced to oppose the senate when it falls under the sway of the ‘Pompeian Party’, in Suetonius his questionable early career is offset by his later ciuilitas and commitment to uphold senatorial authority, while in Tacitus he is a revolutionary who relentlessly undermines the senate and turns the state upside down.